Paciente femenino de 33 años de edad con fibrosis pulmonar más neumonía. - Bonilla Vera, Christian Adonis (2021)
The clinical case deals with a 33-year-old female patient with a personal pathological history of SARS-Cov-2 who presents with a fever greater than 38 ° C, dyspnea, cough with expectoration, chest pain, fatigue, weight loss; Antivirals were prescribed as initial treatment, but there were no positive results, so she was re-examined and prescribed clarithromycin, claricort, and fluimucil for 10 days, plus two rounds per day of nebulization with saline, atrovent and dexamethasone, and oxygen therapy. After performing the corresponding tests, the diagnosis of pulmonary fibrosis + lower respiratory tract infection was reached. The present clinical case seeks to justify the importance of knowing how patients with pulmonary fibrosis can lead a calm life and control the progress of the disease since although it is true there is no cure for this condition, but it is treatable and a person who can sufferers can alleviate their symptoms with care and rehabilitation in the same way avoiding possible complications. The main objective is to show how to help a patient with pulmonary fibrosis to obtain a good quality of life while coping with their disease. It was concluded that these patients are going to be exposed to infections, especially respiratory infections, so it is very important that the patient lives in an environment suitable for their health condition.